1983
DOI: 10.1111/j.1365-2133.1983.tb04594.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ identification of T6-positive cells in normal human dermis by immunoelectron microscopy*

Abstract: Monoclonal anti-T6 antibody, which reacts with the majority of cortical thymocytes but not peripheral T cells, also reacts with human epidermal Langerhans cells, as shown by a four-step immunoperoxidase method and immunoelectron microscopy. To define whether T6-positive cells are also present in normal human dermis, we used these techniques to demonstrate two immunologically distinct populations of histiocyte-like cells in normal human dermis. The first population contains cells devoid of phagolysosomes or Bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The Birbeck granule-negative IDCs are MHC class IIpositive epidermal cells which express the same immunological and cytochemical markers as non-activated LCs, and are therefore considered to be a subset of immature LCs [26,28]. The stimuli necessary for the occurrence of these distinct dendritic cells are not known.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The Birbeck granule-negative IDCs are MHC class IIpositive epidermal cells which express the same immunological and cytochemical markers as non-activated LCs, and are therefore considered to be a subset of immature LCs [26,28]. The stimuli necessary for the occurrence of these distinct dendritic cells are not known.…”
Section: Discussionmentioning
confidence: 98%
“…It has become evident that this and other phenotypic markers of normal LCs change under various conditions, including antigen presentation [1,3,29,33], and therefore do not represent reliable markers for the identification and enumeration of pathologically altered epidermal LCs. Moreover, the indeterminate dendritic cells (IDCs) of the epidermis, which probably represent immature precursors of the LCs [26,28] bear the same markers as normal LCs and can therefore not be distinguished by immunohistological and histochemical staining methods.…”
Section: Introductionmentioning
confidence: 99%
“…The panning method as previously reported by Reinherz et al (1981), Scheynius et al, (1982), Wysocki and Sato (1978) and ourselves (Czernielewski et al, 1983) was used, although it gave only moderate enrichment. Since its first report (Page-Faulk & Taylor, 1971), the immunogold labelling method has been largely used for the identification of cell surface antigens on cell suspensions by immunoelectron microscopy (De Mey, 1983;Horisberger, 1979;Lafferty el al., 1981) including quantitative evaluationsof labelling densities ofvarious cell surface markers (Laffertyi^r a/., 1981). Various advantages of this method can be noted: the absence of non-specific absorption of gold particles on cell surfaces, the possibility of post-staining ultrathin sections without changes in the immunolabelling contrast and of a double labelling using gold particles of different sizes.…”
Section: Quantitative Evaluation Of Epidermal Hla-dr Expressionmentioning
confidence: 99%
“…Perhaps the indeterminate cells with a high density of HLA-DR antigens may represent activated and immature states of LC or functionally distinct subtypes. The T^ antigen is now considered as a highly specific differentiation marker of LC (Chu et al, 1982;Harrist ei al, 1983;Holden, Morgan & MacDonald, 1982;Murphy et al, 1982Murphy et al, , 1983. Monoclonal anti-Te antibody also reacts with dermal indeterminate cells (Murphy ei al, 1983).…”
Section: Quantitative Evaluation Of Epidermal Hla-dr Expressionmentioning
confidence: 99%
“…These authors have also added that extracellular parasites appeared to enhance, both the activation and lytic processes, but degradation of these parasites were associated with dendritic-like cells (DLCs) more than with macrophages. In the present study, typical epidermal Langerhans cells (LCs), which may be related to DLCs, (Chu et al, 1982;Murphy et al, 1983), have been demonstrated in association to type II epithelioid cells. Our observations are also similar to those described for Trypanosoma cruzi (Kress et al, 1975;Noguiera & Cohn, 1976), which tend to escape from the FY to lie free in the host cell cytoplasm.…”
Section: Tuberculoid Granulomasmentioning
confidence: 98%